SPATIAL AND TEMPORAL PATTERNS OF NET CARBON EXCHANGE IN THE POLAR SEMI-DESERT VEGETATION TYPE ON MELVILLE ISLAND, NUNAVUT (2013) - Scott, Neal; Treitz, Paul; Buckley, Emma (Borealis, 2016)
In 2013, eight Automated Soil CO2 Exchange (ACE) Stations were deployed at the Cape Bounty Arctic Watershed Observatory (CBAWO) to quantify the contribution of CO2 exchange from polar semi-desert vegetation. The polar semi-desert vegetation type is of specific interest as it is widely distributed across the High Arctic and there are relatively few studies conducted in the past on its contributions in CO2 exchange. As polar semi-desert vegetation cover varies at relatively small spatial scales, the chambers were distributed between vegetated areas (18-51% cover) and bare soil. The measurements from each chamber were automatically recorded every 30 minutes from May 30 2013 to July 28 2013. Air temperature, soil temperature and soil moisture measurements were also collected in conjunction with the net CO2 exchange rate (NCER). The collected results indicate that respiration is the dominant process of CO2 exchange during the early season, while photosynthesis is the dominant component during the warmer part of the season.